Short Communication: Evaluation of antibacterial activities and phytochemical composition of ethanolic extract of Diplazium esculentum - FESKAHARNY ALAMSJAH; SASQIA FANDINI; MILDAWATI MILDAWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Alamsjah F, Fandini S, Mildawati M. 2024. Short Communication: Evaluation of antibacterial activities and phytochemical composition of ethanolic extract of Diplazium esculentum. Biodiversitas 25: 937-941. Antibacterial agents are crucial in fighting infections by stopping or inhibiting pathogenic bacteria growth. Diplazium esculentum (Retz.) Sw., is a natural resource with great potential in traditional medicine. This study aimed to investigate the antibacterial effectiveness of ethanol extract of D. esculentum against two common bacteria, Pseudomonas aeruginosa and Staphylococcus epidermidis. This research was done using disc diffusion technique with comprehensive phytochemical screening. The results revealed antibacterial properties of the ethanolic extract of D. esculentum against P. aeruginosa and S. epidermidis. The most potent antibacterial activity was observed at 80 and 60% concentrations against P. aeruginosa, resulting in inhibition zones with 5.90 mm and 5.47 mm diameters. A similar pattern was also observed against S. epidermidis, where 80% concentration showed significant efficacy, with an inhibition zone of 5.69 mm diameter. Phytochemical analysis result revealed the presence of various secondary metabolites, including alkaloids, steroids, polyphenols, tannins, flavonoids, and saponins. These phytochemical compounds contribute antibacterial properties and have promising potential for further research to develop natural antibacterial agents.